2015
DOI: 10.1007/s00374-015-0997-0
|View full text |Cite
|
Sign up to set email alerts
|

Soil gross N transformation rates after a wildfire and straw mulch application for burned soil emergency stabilisation

Abstract: Effects of fire and post-fire mulching for soil protection on N transformations were evaluated in the laboratory 4, 8 and 12 months after a wildfire in the 0-2-cm layer of a burned soil without (BS) or with straw mulch (BSM) and an unburned soil (US). The relationships between the gross N rates calculated with the FLUAZ model (Mary et al. 1998) and 19 soil characteristics were also explored. The gross N mineralisation (m) and NH 4 + immobilisation rates (ia) were similar and significantly correlated (p<0.001) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 55 publications
(92 reference statements)
2
8
0
Order By: Relevance
“…The immobilisation of NO 3 − ( I NO3 ) was infrequently modelled in the studied soils, except in those burnt with intermediate severity where it can be, occasionally, the most important NO 3 − consuming process. This result agrees with the fact that, in general, microorganisms immobilise NH 4 + rather than NO 3 − (see Booth et al (2005) and references therein), as also found in other studies with burnt soils (Fernández‐Fernández et al, 2017; Gómez‐Rey & González‐Prieto, 2015). Moreover, NO 3 − immobilisation seems to be suppressed when NH 4 + concentrations are elevated and it tends to be more frequent in microsites where NH 4 + has been depleted (Chen & Stark, 2000).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The immobilisation of NO 3 − ( I NO3 ) was infrequently modelled in the studied soils, except in those burnt with intermediate severity where it can be, occasionally, the most important NO 3 − consuming process. This result agrees with the fact that, in general, microorganisms immobilise NH 4 + rather than NO 3 − (see Booth et al (2005) and references therein), as also found in other studies with burnt soils (Fernández‐Fernández et al, 2017; Gómez‐Rey & González‐Prieto, 2015). Moreover, NO 3 − immobilisation seems to be suppressed when NH 4 + concentrations are elevated and it tends to be more frequent in microsites where NH 4 + has been depleted (Chen & Stark, 2000).…”
Section: Discussionsupporting
confidence: 91%
“…Gross N mineralization is usually stimulated by mulching in unburnt soils between 1 month and 1 year after mulch application (Huang et al, 2008; Murphy et al, 2003; Shindo & Nishio, 2005). In burnt soils, Gómez‐Rey and González‐Prieto (2015) also found an increase of gross N mineralization, but short‐lived: it was observed 4 months after the fire, but not after 8 months. Conversely, Fernández‐Fernández et al (2017) reported a decrease in gross N mineralization in mulched burnt soils both after 3 and 6 months of incubation under humidity and temperature conditions optimal for microbial activity.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…The GNM rate in our study ranged between 1.85 and 4.67 mg N kg −1 soil day −1 , which is consistent with several other studies (1–10 mg N kg −1 soil day −1 ; Cheng et al ., ; Gómez‐Rey & González‐Prieto, ), but it is greater than the rate (0.73 mg N kg −1 soil day −1 ) observed by Nelissen et al . ().…”
Section: Discussionmentioning
confidence: 62%
“…In , 2014 straw application after fire effectively reduced erosion but did not affect the soil nutrient concentrations. Mulching has been shown to affect gross N fluxes in unburnt soils (Cheng et al, 2012;Huang et al, 2008), but we are aware of only one experiment testing the effect of straw application on gross N rates in burnt soils (Gómez-Rey and González-Prieto, 2015). This study with a soil affected by a moderate to highly severe wildfire showed that mulching resulted in a short-lived stimulation of gross mineralisation and gross immobilisation of ammonium (NH 4 + ).…”
Section: Introductionmentioning
confidence: 99%